A usability testing on jawi mobile application for standard one acquisition on reading and writing skills / Siti Shafida Sharifuddin, Nur Hasni Nasrudin and Rosida Ahmad Junid - Siti Shafida, Sharifuddin; Nur Hasni, Nasrudin; Rosida, Ahmad Junid (UiTM Press, 2020)
Usability testing is one of the most profound product-evaluation methods that can be applied to determine the effectiveness of an innovation, especially how the product invented meets the user's need and expectation. However, the problem is that there are some believes that usability testing is pointless because real users would test the application and report any issue arises. Notwithstanding this belief, the researchers still think that usability testing can highlight the quality of user experience and can answer the question of whether people enjoy the application or not. Thus, this paper will expose the readers to the usability testing that is conducted on a new Jawi Mobile Application that adopts Augmented Reality (AR) technology and used ADDIE research method, which aims to improve Standard One student's skills in reading and writing the Jawi script. Thirty students (30) of standard one aged 7 years old from a chosen primary school were involved in the usability test. The usability test involved questionnaires and observations based on four acceptance test elements. Based on the findings, it is proven that the new Jawi Mobile Application that uses Augmented Reality (AR) Multimedia Elements is a breakthrough innovation which firstly, can help to ameliorate standard one basic acquisition on Jawi reading and writing skills, and secondly can be integrated into the Standard One School Syllabus.